Numerical and experimental study of the impeller of a liquid pump of a truck cooling system and the development of a new open-type impeller - Salakhov, Rishat (Array, 2020)
Typically, closed-type impellers are more efficient than open-type impellers, but in the manufacture of closed-type impellers, cost of wheels is higher. This paper describes the development of cost-effective and simple impeller wheel for a fluid pump in the truck cooling system. To perform this task, the numerical computations of a standard impeller wheel were carried out, its characteristics were also obtained from a test bench, the standard impeller wheel model was verified. The open-type impeller wheel was developed according to the current dimensions of standard impeller wheel and then analyzed with the numerical computations by the software ANSYS CFX (Academic license) computational fluid dynamics. The developed open-type impeller wheel works very effectively in spite of performance degradation by 5% in comparison to the closed-type impeller wheel. When working as a part of engine, the pump efficiency is 0.552-0.579. The maximum value of the pump efficiency is 0.579, it can be achieved at the highest speed of the pump (4,548 rpm and 655 l/min).